TRANSFORMATIONAL LEADERSHIP AND EMPLOYEE OUTCOMES: PSYCHOLOGICAL CAPITAL AS MODERATOR - Kresna, Kadek Ardhika Widya; Suryani, Tatik (Kesatuan Press, 2025)
This study aims to analyze the effect of transformational leadership on team member performance and work engagement, as well as psychological capital as a moderating variable, in the context of PT Petrokimia Gresik. Using a quantitative approach and PLS-SEM analysis method, the study findings reveal that transformational leadership positively affects team member performance, both directly and indirectly through increased work engagement. Employees led by transformational leaders show higher emotional and cognitive engagement in their work, which drives increased work performance. Furthermore, psychological capital significantly strengthens the relationship between work engagement and performance, indicating that hope, self-efficacy, optimism, and resilience are important in maintaining team member effectiveness amidst workplace challenges. These findings underscore the strategic importance of fostering transformational leadership styles and investing in team member psychological capital to enhance productivity and ensure sustainable performance in manufacturing organizations. This study contributes theoretically to the literature on organizational behavior and offers practical implications for management in designing interventions that enhance team member engagement and psychological resilience.